Effectiveness of acupuncture in the governor vessel and Yangming meridian for the treatment of acute ischemic stroke: A systematic review and network meta-analysis. - Yingqi Xu; Xiuzhen Xie; Pingping Su; Jiashan Wang; Xinxin Luo; Jianli Niu; Zhuqing Jin (PLoS ONE)
Background Acupuncture of the governor vessel and Yangming meridian are widely used in the treatment of acute ischemic stroke (AIS). However, the optimal meridian for acupuncture in the treatment of AIS remains uncertain. Purpose This network meta-analysis study aimed to compare the clinical effectiveness of acupuncture at governor vessel and Yangming meridian in the treatment of AIS. Methods All relevant studies published in CNKI, WANFANG, VIP, Sinomed, Cochrane Library, Web of Science, Pub Med, and Embase before January 13, 2024 were systematically retrieved. The two researchers independently screened the studies and extracted the data. Cochrane ROB tool was used to evaluate the quality of the studies, and Stata 14.0 software was used to conduct a network meta-analysis of neurological deficit score, activities of daily living (ADL), clinical effective rate and Fugl-meyer motor function evaluation (FMA). Results A total of 401 studies were obtained, and 17 studies met the inclusion criteria. The surface under the cumulative ranking curve (SUCRA) values of the four outcome indexes were all ranked by "Governor vessel acupuncture + Conventional neurology treatment(GVAc+CT) > Yangming meridian acupuncture + Conventional neurology treatment(YMAc+CT) > Conventional neurology treatment (CT)". Compared to YMAc+CT and CT, GVAc+CT had the best effect in reducing the degree of neurological deficit score (SMD = -0.72, 95%CI = [-1.22,-0.21] and SMD = -1.07,95%CI = [-1.45,-0.69], respectively) and promoting the recovery of ADL((SMD = 0.59,95%CI = [0.31,0.88] and SMD = 0.96,95%CI = [0.70,1.21], respectively). Compared to CT, GVAc+CT also had a better clinical effective rate in the treatment of AIS (RR = 1.14,95%CI = [1.04,1.25]). Conclusions Governor vessel acupuncture combined with conventional neurology treatment has the best effect in reducing the degree of neurological deficit score and promoting the recovery of ADL in AIS patientscompared to YMAc+CT and CT. Governor Vessel acupuncture is the most preferable acupoint scheme for clinical acupuncture treatment of AIS.